1991
DOI: 10.1002/app.1991.070430719
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Escherichia coli from water by systems based on insoluble polystyrene–poly(ethylene glycol)s, –polyethylenimines, and –polyethylenepolyamines quaternized

Abstract: Insoluble polymers adsorbing bacterial cells were prepared by reactions of chloromethylated, divinylbenzene crosslinked polystyrene ( CMPS ) beads with poly (ethylene glycol) 600 (PEGGOO), PEG monolaurate (PEGLE) , polyethylenimines ( PEIs, MW = ca. 300, 600, and 1200, referred to as PEI300, PEIGOO, and PEI1200, respectively), as well as ethylenediamine (ED) and tetraethylenepentamine (TEP) as polyethylenepolyamines. CMPS-ED and CMPS-TEP were further quaternized with 1-iodooctane (10) and 1-iodododecane (IDD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…[42] However, Tashiro et al reported bactericidal activity of B-PEI with MW of 600 on E. coli at the concentrations of 25–100 μg/mL in saline. [43, 44] We found that the B-PEI 12 are not active against E. coli (MIC > 1000μg/mL) in MH broth and do not significantly permeabilize the OM of E. coli . However, the lower MW B-PEIs displayed relatively weak inhibitory effects against E. coli (MIC = 250 – 500 μg/mL) although they are also not strong membrane permeabilizers.…”
Section: Resultsmentioning
confidence: 91%
“…[42] However, Tashiro et al reported bactericidal activity of B-PEI with MW of 600 on E. coli at the concentrations of 25–100 μg/mL in saline. [43, 44] We found that the B-PEI 12 are not active against E. coli (MIC > 1000μg/mL) in MH broth and do not significantly permeabilize the OM of E. coli . However, the lower MW B-PEIs displayed relatively weak inhibitory effects against E. coli (MIC = 250 – 500 μg/mL) although they are also not strong membrane permeabilizers.…”
Section: Resultsmentioning
confidence: 91%
“…Insoluble, bacteria adsorbing macromolecules [93] were prepared by grafting of chloromethylated divinylbenzene crosslinked polystyrene beads (CMPS) with poly(ethylene glycol) 600 (PEG600), PEG-mono-dodecyl ether (PEGDD), polyethylenenimines (PEI, MW = ca. 300, 600, and 1 200, referred to as PEI300, PEI600, and PEI1200, respectively), as well as ethylenediamine (ED) and tetraethylenepentamine (TEP).…”
Section: Macromolecules Based On Crosslinkedmentioning
confidence: 99%
“…Only a few studies on the interaction of microbial cells with a brush-type (graftchain-containing) interface have been reported (Kanazawa et al, 1993;Tashiro, 1991). For these brush-type interfaces, the functional groups are not immobilized directly onto the polymeric support but the grafted polymer brushes are.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, researchers have been searching for an alternative water disinfectant, such as a solid polymeric material with microbial-cell-capturing activity, to avoid the problem of residual toxicity of soluble chlorine (Kawabata et al, 1983;Tashiro, 1991).…”
Section: Introductionmentioning
confidence: 99%